Bioprospection of biocompounds and dietary supplements of microalgae with immunostimulating activity: a comprehensive review - Arialdo M. Silveira Júnior; Silvia Maria M. Faustino; Alan C. Cunha (PeerJ, 2019)
The objective of this review is to analyze the role of microalgal bioprospecting and the application of microalgae as food supplements and immunostimulants in global and regional aquaculture, highlighting the Brazilian Amazon. This study evaluates the primary advantages of the application of the bioactive compounds of these microorganisms, simultaneously identifying the knowledge gaps that hinder their biotechnological and economic exploitation. The methodology used is comparative and descriptive-analytical, considering the hypothesis of the importance of bioprospecting microalgae, the mechanisms of crop development and its biotechnological and sustainable application. In this context, this review describes the primary applications of microalgae in aquaculture during the last decade (2005–2017). The positive effects of food replacement and/or complementation of microalgae on the diets of organisms, such as their influence on the reproduction rates, growth, and development of fish, mollusks and crustaceans are described and analyzed. In addition, the importance of physiological parameters and their association with the associated gene expression of immune responses in organisms supplemented with microalgae was demonstrated. Complementarily, the existence of technical-scientific gaps in a regional panorama was identified, despite the potential of microalgal cultivation in the Brazilian Amazon. In general, factors preventing the most immediate biotechnological applications in the use of microalgae in the region include the absence of applied research in the area. We conclude that the potential of these microorganisms has been relatively well exploited at the international level but not at the Amazon level. In the latter case, the biotechnological potential still depends on a series of crucial steps that involve the identification of species, the understanding of their functional characteristics and their applicability in the biotechnological area, especially in aquaculture.